REKONSTRUKSI ETIKA PROFESI PENDIDIK BERBASIS KARAKTER ISLAMI UNTUK MASA DEPAN PENDIDIKAN - Novia Nurhayati; Haris Riadi; Fela Sophia (Jurnal Manajemen Pendidikan, 2026)
This research aims to examine and formulate a concept for reconstructing teaching professional ethics based on Islamic character as a response to the challenges of education in the digital era of Society 5.0. This research is motivated by the crucial role of educators, who serve not only as conduits of knowledge but also as role models in shaping students' character with noble morals. Rapid technological developments provide various benefits, but also present challenges in the form of a decline in moral values, making strengthening teaching professional ethics based on Islamic values ​​necessary. The method used in this research is a literature review, examining various relevant literature sources, such as books, journals, and scientific articles. The results indicate that teaching professional ethics based on Islamic character requires integrating the values ​​of faith, morals, charity, role models, social values, and aesthetics into educational practice. Efforts to reconstruct teaching professional ethics are carried out through strengthening spiritual and moral values ​​and increasing the ability to adapt to technological developments. Thus, the integration of professional ethics, professionalism, and Islamic educational values ​​is expected to produce a quality education system and produce a generation that is intelligent, noble, and highly socially conscious.